PEMAKNAAN LAGU WAJIB NASIONAL TERHADAP KARAKTER CINTA TANAH AIR SISWA KELAS V SDN 10 TIGA DESA - Evi Prianti Evi; Felisitas Viktoria Melati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The decline of nationalism among elementary school students has become one of the challenges faced by Indonesian education in the era of globalization. National compulsory songs are one of the educational media that contain values of patriotism, unity, and love for the homeland. However, students often sing these songs merely as a routine activity without understanding their meaning. This study aimed to describe students' perceptions of national compulsory songs, analyze the meaning of these songs in strengthening students' patriotic character, and identify the challenges faced by teachers in internalizing patriotic values. This research employed a descriptive qualitative approach conducted at SDN 10 Tiga Desa. The participants consisted of the principal, the fifth-grade teacher, and fifth-grade students. Data were collected through observations, semi-structured interviews, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and conclusion drawing. The findings indicate that students generally understand national compulsory songs as symbols of respect for Indonesia and national heroes. The songs contribute to strengthening students' patriotic character through habitual singing activities before lessons and during flag ceremonies. Students demonstrate respect toward national symbols, discipline, cooperation, and environmental responsibility. Nevertheless, several obstacles remain, including students' limited understanding of song lyrics, the influence of popular culture, and the tendency to regard singing activities as mere routines. Teachers address these challenges by explaining the meanings of song lyrics, providing role models, integrating patriotic values into classroom learning, and conducting continuous character-building activities. Therefore, national compulsory songs remain relevant as an effective medium for strengthening patriotic character in elementary schools when accompanied by meaningful learning processes.